Is social identity theory enough to cover sports fans’ behavior?: additional perspective from identity fusion theory - Koo, Taeyeon; Kwon, Hyungi Harry; Shin, Jaeeun; Baeck, Juhae (Frontiers in Psychology, 2025)
This paper investigates the applicability of identity fusion theory (IFT) in explaining sports fan behaviors, highlighting its advantages over traditional frameworks such as social identity theory (SIT) and role identity theory (RIT). While SIT and RIT provide significant insights into group identification and role-based behavior, they fall short in addressing the profound emotional and relational dimensions of sports fandom. These limitations are particularly evident in contexts involving extreme loyalty, self-sacrificial actions, and the deep personal connections fans form with their teams and fellow supporters. IFT bridges these gaps by positing that personal and group identities can merge, creating a powerful motivational force that drives fans to prioritize the group’s welfare as their own. This paper explores how IFT’s dual focus on relational and collective ties offers a more nuanced understanding of fan loyalty, pro-group behavior, and the intense emotional investment characteristic of sports fandom. By examining the interplay of these ties, this paper provides theoretical and practical implications for advancing research on fan engagement and loyalty. The findings suggest that IFT not only complements but extends the explanatory power of SIT and RIT, offering a comprehensive framework for understanding the unique dynamics of sports fandom.